2011
DOI: 10.1177/1468797611412065
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cultural Distance in Mediating the Host Gaze

Abstract: The Contact Hypothesis suggests that contact between people of different cultural backgrounds may result in positive and negative outcomes. As people are more likely to develop social contact with their own national group, or those with a similar background, it was posited that Dutch hosts were more likely to develop positive social contact with German tourists than with East Asian tourists. Our in-depth interviews with Dutch tourism-related business participants suggested the opposite. Furthermore, it was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 47 publications
(41 reference statements)
7
68
1
1
Order By: Relevance
“…For example, in urban Lhasa, "foreigners" were most preferred as visitors to the world heritage sites and religious sites, while "Han people from middle and west China" were preferred more for non-religious sites and buying Tibetan medicine. This finding revealed that the young hosts have formed some stereotypes towards different groups of tourists, which might mediate by cultural distance in a nuanced way (Moufakkir, 2011). Meanwhile, this finding supported the idea that hosts are selective in showing off their cultures, and in some situations, they build "front stages" for tourists and "back stages" for themselves (MacCannell, 1973).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…For example, in urban Lhasa, "foreigners" were most preferred as visitors to the world heritage sites and religious sites, while "Han people from middle and west China" were preferred more for non-religious sites and buying Tibetan medicine. This finding revealed that the young hosts have formed some stereotypes towards different groups of tourists, which might mediate by cultural distance in a nuanced way (Moufakkir, 2011). Meanwhile, this finding supported the idea that hosts are selective in showing off their cultures, and in some situations, they build "front stages" for tourists and "back stages" for themselves (MacCannell, 1973).…”
Section: Discussionsupporting
confidence: 64%
“…For example, Huang and Lee (2010) studied visual evidence from the documentary Cannibal Tours (1988), and examined the diverse gazes (including tourist gaze, the local gaze and the second gaze) in the context of tourism. Moufakkir (2011) checked the mediating function of cultural distances during the local gaze by empirically assessing how Dutch hosts differently viewed German tourists and Asian tourists.…”
Section: Literature Review: Host Gaze Towards Touristsmentioning
confidence: 99%
“…Long-haul international travel by Asian tourists is still mostly practiced in groups (Moufakkir, 2011;Wong and Kwong, 2004). Japanese overseas tourists set this pattern from early on (Carlile, 1996), and it was also adapted by long-haul tourists from other Asian countries such as China, Korea, Thailand and Indonesia (March, 2000).…”
Section: Constellations Of Long-haul International Tourism From the Ementioning
confidence: 99%
“…Within the tourism field, cultural distance has been used to explain guest and host interaction in tourism services from the hosts' perspective (Moufakkir, 2011), behavior of travelers (Crotts, 2004), and destination choice (Ng, Lee & Soutar, 2007) Ng et al presented here, the travel experiences and preferences of the participants is likely a player in these results as well.…”
Section: Tourism Research Related To Cultural Distancementioning
confidence: 90%